Antithrombin Dosing Guidelines in Children Underestimate Dose Needed for Plasma Level Increase. Issue 8 (August 2020) - Mattke, Adrian C.; Johnson, Kerry E.; Parker, Suzanne; Stocker, Christian; Gibbons, Kristen; Schibler, Andreas
Abstract : Objectives: Antithrombin is a cofactor in the coagulation cascade with mild anticoagulant activity and facilitates the action of heparin as an anticoagulant. Antithrombin concentrate dosing guidelines vary but most commonly suggest that each unit of antithrombin concentrate per body weight increases the plasma antithrombin level by 1.5% to 2.2% (depending on manufacturer). We aimed to establish a dosing recommendation dependent on age and disease state. Design: A retrospective analysis of all antithrombin concentrate doses over a period of 5 years. We calculated the increase any respective antithrombin concentrate dose achieved, indexed by body weight, and performed a multivariable analysis to establish independent factors associated with the effectiveness of antithrombin concentrate. Setting: A PICU at a university-affiliated children's hospital. Patients: One hundred fifty-five patients treated in a PICU. Interventions: None. Measurements and Main Results: The effect of 562 doses of antithrombin concentrate on plasma antithrombin levels administered to 155 patients, of which 414 (73.7%) antithrombin concentrate doses administered during extracorporeal life support treatment, were analyzed. For all patients, each unit of antithrombin concentrate/kg increased plasma antithrombin level by 0.86% (SD 0.47%). Plasma antithrombin level increase was influenced by body weight (increase of 0.76% [interquartile range, 0.6–0.92%] for patients < 5 kg; 1.38% [interquartile range, 1.11–2.10%] for > 20 kg), disease state (liver failure having the poorest antithrombin increase) and whether patients were treated with extracorporeal circulatory support (less antithrombin increase on extracorporeal life support). Heparin dose at the time of administration did not influence with amount of change in antithrombin level. Conclusions: Current antithrombin concentrate dosing guidelines overestimate the effect on plasma antithrombin level in critically ill children. Current recommendations result in under-dosing of antithrombin concentrate administration. Age, disease state, and extracorporeal life support should be taken into consideration when administering antithrombin concentrate.